CUSTOMER PREFERENCE AND SATISFACTION LEVEL TOWARD ORGANIC VEGETABLE ATTRIBUTE (CASE STUDY ON TOP BUAH SEGAR CIBUBUR) - Evy Fausiah; Ma’mun Sarma; Mukhamad Najib (Indonesian Journal of Business and Entrepreneurship (IJBE), 2021)
With the increasing public awareness of healthy lifestyles, the demand for organic agricultural products, especially vegetable products, currently continues to increase day by day. Therefore, it will require sufficient information and knowledge about the characteristics, preferences, and satisfaction of consumers with the attributes of organic vegetables to be used as a basis for understanding the needs for organic vegetable consumption. This study aimed to analyze consumer preference for organic vegetables and consumer satisfaction with organic vegetables' attributes. The data collection method used was the purposive sampling technique through distributing questionnaires to 140 respondents. Meanwhile, the data processing methods used in this study were conjoint analysis, IPA, and CSI. The result of the calculation of customer preference in this research showed that packaging was an indicator that had the highest level of importance at 28.99 percent. Hence, it needs innovation by describing the benefits and nutritional content of organic vegetables to increase consumer appeal. Based on IPA results, two attributes' performance had the highest priority to be improved by the company: affordable organic vegetable prices and organic vegetable discounts. Thus, the discounted prices are needed on specific days such as the Anniversary of the company and holidays. Furthermore, based on the CSI calculation results, the customers were considered satisfied with the performance of Top Buah Segar Cibubur. Keywords: CSI, IPA, customer preference, customer satisfaction, organic vegetables